STEAMING TECHNOLOGY RATION PRODUCT IMPLEMENTATION AT PADJADJARAN LOCAL DUCK ON THE METABOLIZABLE ENERGY, DIGESTIBLE ORGANIC MATTER AND PROTEIN RATION VALUE - Emy SAELAN; Tuti WIDJASTUTI; Iwan SETIAWAN; Hendi SETIYATWAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The implementation of ration product from steam technology at Padjadjaran local ducks on the metabolizable energy, digestible organic matter and protein ration value have been done in cage experiment and poultry production laboratory, while the metabolic and digestible test at Ruminant Nutrition and Chemical Feed, Faculty of Animal Husbandry Padjadjaran University, Jatinangor, Sumedang-West Java. The objective of the research is to have the metabolic energy, organic matter digestibility and protein ration value. The experiment has been conducted by using 20 birds local ducks Padjadjaran 18 weeks which birds obtained from Batujajar people farm area, West Java. The research methods used Student's t-test with two treatments and 10 replications, where R0 = ration without steam (control), and R1 = steam ration (Steel and Torrie, 1991). The metabolizable energy of steam ration (2684.64 kcal/kg) was significantly different (P<0.05) more highly significant than without steam (2075.60 kcal/kg). The Organic digestibility matter (95.43%) was significantly different (P<0.05) more highly than without steam (90.86%). The average of protein value digestibility which come from steam ration (71.19%) was significantly different (P<0.05) more highly than without steam (64.07%)